Determinação de parâmetros físico-químicos de bebida fermentada de malte tipo cerveja produzida sem lúpulo e com adição de cacau - Paralovo, Lara Lima (2019)
Using new vegetable sources as a substitute for hops in beer production, in addition to reducing its cost of production opens up possibilities to innovate the brewing market, making it possible to elaborate a drink with different flavors and aromas. This study aimed to produce a beer-like fermented beverage without addition of hops, using Quassia amara L. as bitterness agent and compare the physical and chemical parameters of the addition of varied concentrations of cocoa nibs in maturation step, and even compare the test results with beers Stout and Porter styles found on the market. Six samples were analyzed, containing 0, 1, 2, 3, 4 and 5 grams of cocoa per liter of beer, all produced with 0.25 g.L-1 of Quassia amara L. All samples were analyzed as the phenolic (mg EAG.L-1 ) and protein content (mg.L-1 ), the 600 nm absorbance, pH, alcohol content (%v/v) and color (°EBC). The formulations of 0 to 5 g.L-1 of cocoa nibs resulted in protein values between 640.27 and 668.70 mg.L-1 , phenolic compounds between 1586, 86 e 1639,69 mg EAG.L-1 , absorbance between 1.291 and 1.451, pH between 3.67 and 3.72, color between 60.77 and 65.95 °EBC and alcohol content between 5.615 and 5.791, all classified as beer with high alcohol content. When comparing the beverage prepared with those acquired in the market it was concluded that the same approaches as the color and alcoholic content of beer styles Porter and Stout.